Development of a Model for Prediction of Composition and the Atomic Weights of the Elements (Global Journal of Medical Research, 2022)
Initially, a summary of the three works recently published by the author was presented, emphasizing aspects related to the topic addressed in this article. Considering that proteins are the #x201C;fundamental particles#x201D; of all living biological beings and that atoms are the fundamental particles of all matter existing in the universe, the author had the intuition that the DNA code was created in the molds of a pre-existing universal code, hence the idea that the universal code, that is, the code of atoms, was similar to the code of DNA. Based on these assumptions, he developed a model similar to the DNA genetic code model for predicting the composition and atomic weights of atoms. Simulations made considering the elements of the Periodic Table seem to confirm the model developed by the author. The atoms generated by the model, called #x201C;genetic atoms#x201D;, generated from the active genetic groups, allow the prediction of the subatomic composition of the various elements of the Periodic Table, the possibility of the existence of numerous unmarked isotopes and provides a possible explanation for so many subatomic particles. If the model is confirmed, new questions are raised, some of which are cited by the author.
Keywords: modeling; simulation; composition; atomic weight